Ignition mechanism of methane by 5G electromagnetic waves and power safety thresholds in underground coal mines - Yong ZHANG; Jijian MENG; Xiangyuan CHEN; Xiaofeng WANG; Xiaojing CHEN; Haijian CHEN; Ziwen GUO (Meitan xuebao)
5G technology, with its advantages of high bandwidth, low latency, and extensive connectivity, has shown great potential in driving the intelligent transformation of the coal mining industry. This study systematically investigates the potential risk of methane gas explosions triggered by 5G RF signals in underground coal mines and the limitations of current standards for 5G RF applications. First, existing explosion-proof standards were traced and analyzed to clarify their historical evolution and scope. An evaluation system for the safety thresholds of RF device transmitters in underground coal mines was then established. Subsequently, a universal calculation model for electromagnetic wave power safety thresholds in air/methane mixtures was developed by integrating low-temperature plasma dynamics, electromagnetic wave propagation theory, and methane explosion reaction kinetics. Through parametric matching design of a half-wave dipole antenna, efficient RF energy coupling to the discharge electrode was achieved, and laboratory experiments were conducted to ignite methane gas. The results demonstrated that RF energy can ignite methane, and the safety threshold is influenced by multiple factors, including modulation mode, frequency, temperature and humidity, energy accumulation, antenna gain, and multi-source superposition. The study found that the power safety threshold for the 5G NR 700 MHz band is not lower than 43.3 W. When evaluating the safety threshold based on the transmitter, the impact of antenna gain can be neglected. A method based on correlation coefficients and antenna diversity was developed to effectively quantify the impact of multi-source superposition on safety evaluations, indicating that under certain conditions, the effect of multi-source superposition can be ignored, thereby improving the utilization efficiency of RF power. This study clarified the power safety threshold for 700 MHz 5G base stations in underground coal mines, provided a reference for the safety research of other frequency bands and RF devices, and emphasized the necessity of revising relevant standards. Such revisions aim to precisely assess the risk of RF signals igniting flammable gases in complex underground environments, thereby supporting the intelligent transformation and safe production of the coal mining industry.